2016
DOI: 10.1016/j.heliyon.2016.e00078
|View full text |Cite
|
Sign up to set email alerts
|

The policy implications of urban open space commercial vegetable farmers’ willingness and ability to pay for reclaimed water for irrigation in Kumasi, Ghana

Abstract: The acute waste management problems, coupled with the proliferation of small scale industries in many developing countries, make low quality water treatment before use inevitable in the long run. These industries have the potential to discharge effluent containing chemicals and heavy metals into the environment. The indiscriminative use of pharmaceutical products by households in many of these countries is another source of health concern. Low quality water treatment in these countries has however been hampere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Results from this research (Bansah and Suglo, 2016) met recommended microbiological and chemical quality guidelines for wastewater reuse in Ghana. The question of whether farmers engaged in urban and peri-urban farming are willing to pay for treated or recycled water was answered by Amponsah et al (2016). They reported that approximately 60 % of vegetable farmers would pay for treated water for their irrigation at a fee.…”
Section: Wastewater Treatment and Reuse In Ghanamentioning
confidence: 99%
“…Results from this research (Bansah and Suglo, 2016) met recommended microbiological and chemical quality guidelines for wastewater reuse in Ghana. The question of whether farmers engaged in urban and peri-urban farming are willing to pay for treated or recycled water was answered by Amponsah et al (2016). They reported that approximately 60 % of vegetable farmers would pay for treated water for their irrigation at a fee.…”
Section: Wastewater Treatment and Reuse In Ghanamentioning
confidence: 99%
“…The expansion in urban populations in many countries in the world has resulted in massive volumes of wastewater. These wastewaters are released in open places due to a lack of financial capacity and overall awareness about wastewater management (Amponsah et al, 2016). Municipalities use some of these polluted wastewaters for plant growth and other uses.…”
Section: Introductionmentioning
confidence: 99%
“…Reclaimed water is an important means to resolve the short-term problem of water resources, and has already been applied in many countries [4][5][6] . At present, reclaimed water drip irrigation is being used in Beijing, China, to alleviate local water shortages [7,8] .…”
Section: Introduction 1mentioning
confidence: 99%